Analysis Of Benefits On Using The Marketplace For Village MSMEs - Trufi Murdiani; Muhammad Ariza Eka Yusendra; Supriyadi Supriyadi; Muhammad Galih Ramaputra (Prosiding International conference on Information Technology and Business (ICITB), 2022)
In an effort to spur the development and growth of small business actors or MSMEs, a certain method is needed to increase their products sales. One of the efforts that have made is utilizing digital media which has been rapidly develop online by many business actors. The problem that arises is how to use the digital media such as marketplace as the most effective tool in order to increase marketing activities since some MSMEs actors still do not able to use marketplace for doing business. This research is done to prove the effectiveness of digital marketing media in the form of a marketplace for small business people in Jati Indah Village, South Lampung, who are directly involved with online marketing. The method was qualitative method and have done by interview approaches to some SME actors in Jati Indah Village. By the datas that acquared from interview, the analysis on the problem was done as well as the step in finding the solution on how to achieve the success in using digital media namely marketplace. Through this research, it is expected that small businesses can choose wisely and effectively the use of digital media namely marketplace in their marketing activities so the sell of their product will increase.  Keywords—Marketplace, small business, digital marketing